Deliberation Online: An Impediment Against Fundamentalism Offline? - May Thorseth (Oñati Socio-Legal Series)
The opposition between fundamentalism and deliberative democracy is basic to the argument of this article. In the following we shall take our point of departure in a procedural understanding of fundamentalism that enables us to see how different substantive values might turn out to be fundamentalist. Any form of communication that obstructs possible change of preferences might be fundamentalist. The decisive criterion is thus not to point out particular forms of communication as fundamentalist or deliberative per se; the decisive criterion is how the communication works.